Essentials of corporate performance measurement - Friedlob, G. Thomas (Wiley, 2002)
Includes bibliographical references (p. 197-198) and index; Preface -- Acknowledgments -- The importance of return on investment: ROI -- Using ROI to analyze performance -- ROI and decision making -- Variations of ROI -- Analyzing sales revenues, costs, and profits -- ROI and investment centers -- Return on technology investment: ROTI and ROIT -- Residual performance measures: RI and EVA -- Notes -- Index